The multiple faces of autoimmune Addison’s disease in children - Capalbo, Donatella; Esposito, Andrea; Gaeta, Valeria; Lorello, Paola; Vasaturo, Sara; Di Mase, Raffaella; Salerno, Mariacarolina (Frontiers in Endocrinology, 2024)
Primary adrenal insufficiency (PAI) is a rare medical condition, characterized by deficiency of adrenal hormones. Although rare, PAI is a life-threatening disease requiring prompt recognition and treatment. However, symptoms of PAI are often non-specific and diagnosis can be challenging causing frequent diagnostic delay. In adults autoimmunity is the most common cause of PAI in industrialized countries, while in children the most frequent etiology is represented by congenital defects of steroidogenesis and, in particular, by congenital adrenal hyperplasia (CAH) due to 21hydroxylase deficiency. Few recent case series from different countries have reported that following CAH autoimmunity is the second most common etiology of PAI in pediatric age group. However data on autoimmune primary adrenal insufficiency in children are still scanty and the exact epidemiology, clinical manifestations and long term outcomes of this condition has still to be defined.The scope of this review is to summarize current knowledge on etiology, presentation and treatment of autoimmune PAI in childhood and to increase physicians' awareness on this on signs that should raise an early suspicion of this condition.